CORRELATIONS OF MOTOR DIMENSIONS OF STUDENTS OF THE FACULTY OF SPORT AND PHYSICAL EDUCATION WITH TEACHING CONTENTS OF SPORTS GYMNASTICS - Jovica Petković; Aldijana Muratović; Gabrijela Doina Tanase (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Sports gymnastics, as a basic sport discipline, has been largely neglected through the work with young people in primary and secondary school. This is one of the key reasons for the multitude of problems, with which students of the Faculty of Sport and Physical Education face, when it comes to mastering the content of sports gymnastics. Development of strength, speed, coordination, balance and flexibility are very important and dominant factor in mastering gymnastic skills and program contents, especially when it comes to gymnastics parterre, where a greater degree of motor preparedness also affects the breaking of fear as the disruptive factor in the training process.